Fractal zeta functions and fractal drums : higher-dimensional theory of complex dimensions /: higher-dimensional theory of complex dimensions. (2017) - Lapidus, Michel L (Michel Laurent), 1956-; Radunović, Goran; Žubrinić, Darko
No abstract available